The importance of interreligious dialogue in Nigeria : (Muslim- Christian relations) - Ashimi, Tijani Ahmad (International Islamic University Malaysia, 2011)
Nowadays and in this twenty first century, Inter-religious dialogue is gaining momentum and importance at both national and international levels. Perhaps, that is due to its role and goal in building bridges among different religious groups to promote respect, tolerance and peaceful living. Based on above fact, inter-religious dialogue is perhaps; more important in Nigeria than anywhere else, on the grounds that, Nigeria is considered as the most populous country in African continent, and it is moreover, a pluralistic and multi religious society, which is mainly dominated by Islam and Christianity. Yet, in modern Nigeria, the relation between Muslims and their counterpart Christians is in continuous jeopardy (if not deteriorating). As such, the country has experienced various religious violence between these two dominant religious groups, (Islam and Christianity) and these religions are even sometimes depicted as monolithic entities that confront each other in pitched battles. As a result of uncountable battles and confrontations, incalculable human loses and material damages are always attributed to religion. It is important to mention at this juncture, that there is no a meaningful dialogue that has taken place in modern Nigeria, the only existing dialogues that are based on academic conferences and individual efforts seem to be ineffective .As far as peaceful coexistence is concerned, and as far as religious tolerance is also important, there is no doubt that the best forum to promote Muslims-Christians relationship, and the right tool to tackle reoccurrence of religious conflict in the country is sound interreligious dialogue. Thus, this humble paper will demonstrate the meaning of inter-religious dialogue according to various scholars, Quranic and Biblical perspectives of interreligious dialogue will be explored, a discussion about interreligious dialogue in Nigeria will also be made, and that will be followed by causes behind the need for sound and effective inter-religious dialogue in Nigerian context. Lastly, the article will provide effective methods guidelines and some action guides that can be utilized to achieve the goal of this forum in Nigerian pluralistic society.